A concept paper on potential behavioural factors that influence the Global Positioning System (GPS) usage in small-scale fishing operation - Bolong, Jusang; Ahmad Ghazali, Akmar Hayati; Shah, Jasmin Arif (Human Resource Management Academic Research Society, 2023)
The main objective of this study is to review potential behavioral factors that influence the use of The Global Positioning System (GPS) in small-scale fishing operations. This study is based on three main problems. First, although the GPS 'marking' function can help fishermen overcome their two main issues, namely low income and the threat of climate change, they still do not use this technology satisfactorily. Second is the need for review to understand the GPS use in small-scale fishing operations. Third, the need to provide ideas to improve further the Fishermen's Transformation Program developed by the government. The present review explained factors in models or theories such as the Extended Technology Acceptance Model, the Unified Theory of Acceptance and Usage of Technology, and a couple of previous studies that explain certain potential factors that can influence GPS usage in fishing activity. To review of what factors influence fishermen's usage of GPS is very important because it can then be used by the parties concerned in devising strategies to encourage the embrace of advanced technology usage within fishing operations and to ensure that the fishermen are not left behind in using the latest technology which in turn provides excellent benefits to their lives.